A Principal-Agent Approach for the Effective Design of a Renewable Energy Incentive for a Heavily Subsidized Residential Sector: The Case of Qatar - Sikandar Abdul Qadir (17947799) (2023)
Qatar’s per capita electricity consumption is one of the highest in the world, mainly due to the availability of heavily subsidized electricity. The residential sector alone accounts for 60% of produced electricity. The effectiveness of imposing regulatory measures that aim to reduce consumption, such as carbon pricing and rebates, depends on the design of the introduced policy, region dynamics, and population characteristics. Using principal-agent theory, this study addresses the agency problem between the government and households by proposing a policy that aims to incentivize households to shift towards renewable energy sources and reduce their overall energy demand. The study quantifies the potential impact of the policy over a period of five years and estimates that 495 GWh of electricity could be saved, resulting in a significant reduction of 203,710 Tons of CO2e emissions. The cost of implementing the policy is estimated to be 0.838 billion Qatari riyals. The effect of varying model parameters on incentive design is investigated, and a detailed financial analysis is conducted based on the redirection of saved energy resources from domestic consumption to international exports of gas and electricity. Other Information Published in: IEEE Access License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3255105